Meningkatkan Keterampilan Toilet Training Melalui Metode Latihan bagi Anak Autis - Nurul Afifah; , Megaiswari Biran Asnah (Universitas Muhammadiyah Enrekang, 2021)
Autistic children need special attention, one of the most self-sufficient everyday activities of self-reliance, the training toilet. The self-reliance toilet training in autistic children is very low because of developments that affect their brain function. But it can be enhanced by the proper learning methods it can afford. The study was to improve training toilet skills by training methods for elementary school children in SDIT Luqman Padang. The method used in the study is experimental methods through the design of the single subject research (SSR) approach A-B-A. The data collection technique used was by observation, by direct observation of the development of the child training toilet. Research shows that practice methods can improve toilet training skills on autic children shown with changes in the ability increased from the baseline (A1), the intervention (B) and the baseline (A2) phase. The increased ability of the autic toilet training children can be seen from the percentage of achievement obtained ata child's initial ability (A1) children get 16%, the intervention results (B) go up to 72% and the baseline (A2) result gets 88%.